A Review: Fundamental Aspect of Health Protocol Obedience for Preventing COVID-19 Transmission in Indonesia - Ulisis Maradona Tarigan; Aris Widayati (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Coronavirus disease 2019 (COVID-19) is a communicable disease that occurs in respiration systems from one to another human through droplets and direct contact with 4.216.728 cases confirmed on October 1, 2021. Employing the number of cases, the Indonesian Government has made some efforts to improve health protocol compliance. The rate of compliance in every individual is affected by factors such as motivation, severity perception, knowledge, the impact of change, culture, satisfaction level, and health service quality obtained. In this review, we examine the factors which play a role in patient compliance based on the number of works of literature as research material. The search was carried out by searching national and international published scientific journals in the past 2 years (2020 – 2021) with the keywords Compliance, COVID-19 Health Protocol, and Indonesian people through the Google Scholar database. The results from various references show there are fundamental factors in Health Protocol compliance such as positive barriers, knowledge, health status, and awareness level. The level of awareness affects the compliance with health protocol and may make it more easily prevent the spread of COVID-19. The awareness is also affected by the educational level in society.